Assessment of TP53 Polymorphisms and MDM2 SNP309 in Premenopausal Breast Cancer Risk. Issue 3 (23rd January 2017) - Samuel, Nardin; Id Said, Badr; Guha, Tanya; Novokmet, Ana; Li, Weili; Silwal‐Pandit, Laxmi; Børrsen‐Dale, Anne‐Lise; Langerød, Anita; Hudson, Thomas J.; Malkin, David
Abstract : Exploring the germline genetic contribution to inherited early‐onset breast cancer is a cornerstone of research into the etiology of this disease. Our study reports on the composite effect of polymorphic variants in genes implicated in breast cancer risk and demonstrate that variants at polymorphic loci alone are not alone sufficiently pathogenic. These variants may interact with genetic mutations that are yet to be discovered and/or complex haplotypes to confer cancer risk. ABSTRACT: Germline polymorphic variants in cancer predisposition genes such as TP53 have been shown to impact the risk of premenopausal cancer. Accordingly, the aim of this study was to assess the spectrum of polymorphisms in TP53 and its negative regulatory gene, MDM2 (SNP309:T>G) in patients with premenopausal breast cancer. Our findings in a cohort of 40 female patients demonstrate no significant correlation between the studied polymorphisms and risk of premenopausal breast cancer. Although one polymorphism is found in high frequency in this cohort (rs1800372:A>G, 9.0%), it was not associated with the risk of developing cancer before the age of 35 years in an extended cohort of 1, 420 breast cancer cases. Functional studies of the rs1800372:A>G polymorphic allele reveal that it does not affect p53 transactivation function. Further study of variants or mutations in other cancer susceptibility genes is warranted to refine our understanding of the germline contribution to premenopausal breast cancer susceptibility.